Heritage and Entrepreneurship: The Case of Mohan Biscuit Udhyog, Dhankuta, Nepal - Vaidya, Rashesh (Social Science Studies, 2024)
Research Aims: This case study explores the ‘Mohan Biscuit Udhyog’ in Dhankuta, Nepal, a traditional, small-scale business that has become a cultural symbol and popular gift. Despite expansion challenges, including the impact of COVID-19, the business has maintained its appeal by preserving its artisanal approach, relying on community-driven marketing, and considering trademarks to protect its key products against competition.   Design/methodology/approach: The paper has adopted a single case study research design. A single case study research design is a collective term for an in-depth analysis of a small non-random sample (Hunziker & Blankenagel, 2021). Among 15 biscuit industries operating at Dhankuta, only one biscuit industry, Mohan Biscuit Udhyog’, is taken as sample for the case study for the paper.   Research Findings: The study highlights the role of heritage-based enterprises in fostering community identity, sustainable production, and cultural preservation, suggesting that similar rural businesses can succeed by emphasizing quality, local heritage, and community engagement. This case underscores the potential of rural entrepreneurship in creating culturally significant brands that contribute both economically and socially to their regions. Over time, despite having varieties of products, Dhankute Coconut Biscuits have grown in popularity, attributed to their unique firewood-baked flavor, traditional production methods, and a strong local reputation sustained through word-of-mouth marketing. This shows how a single product can maintain the image and continuity of the small-scale business.   Theoretical Contribution/Originality: This case study of Dhankute Coconut Biscuits exemplifies how traditional businesses, rooted in community and heritage, can create lasting economic and cultural value, offering valuable insights into the intersection of local entrepreneurship and cultural preservation.